Strategi Pemasaran Brothers Café dalam Membangun Brand Image Bagi Pengunjung Di Kota Medan - Putra Rahmat Hidayat; Syafruddin Ritonga; Agung Suharyanto (Universitas Medan Area, 2020)
The purpose of this study was to determine the marketing communication strategy undertaken by Brothers Cafe in building brand image for visitors in Medan and its supporting factors and obstacles. The research method is a descriptive qualitative data collection technique with methods of observation, interviews, library research, and documentation. The results of marketing communication strategy research conducted by Brothers Cafe to build brand image, present European-style concepts with a western theme, present a unique menu with an international standard, conduct event programs on holidays, utilize social media such as Instagram and others, work with communities and companies Other companies and factors that support marketing communication strategies in building brand image for visitors in Medan are promotional activities in building brand image for visitors, including locations in office centers, and office buildings, providing facilities, comfortable decoration, presence Special discount for customers who become members. The inhibiting factors of the Brothers cafe marketing communication strategy in building brand image for visitors in Medan are issues such as adulteration, nutritional problems, halal and haram, everyone's tastes are completely different, operational costs rise at any time, sufficient business competition strict. The conclusion obtained by the marketing communication strategy that Brothers cafe did in building brand image for visitors in Medan through promotional activities.